Confidence and the Erosion of Confidence: Economic Functions and Effects - Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2004)
Trust or likewise "confidence" (the term preferred in this paper) are notions which have received considerable attention by economists in the last 8-10 years. In this contribution, much emphasis is put on the understanding what we really mean by "confidence", what the differences between optimism and confidence are and how the onset of confidence can possibly be explained. Also, we analyze the economic effects of a lack of or the erosion of confidence. The paper intends to provide a comprehensive view on the major effects of confidence on economic growth, the business cycle, its relation to income distribution, etc. Finally, the contribution of confidence to social capital is discussed and the erosion of confidence within, between and towards business enterprises as a consequence of the widespread scandals in the US and other industrialised countries at the beginning of the new millennium is portrayed. – – Vertrauen (im Englischen: "Trust" oder auch "Confidence") ist ein Begriff, der sich in den letzten 8 bis 10 Jahren auch unter Ökonomen einer bemerkenswerten Aufmerksamkeit erfreut. In diesem Beitrag wird Vertrauen zunächst als ökonomisches Erfahrungs- und Erkenntnisobjekt vorgestellt. Anschließend diskutieren wir u. a. die Unterschiede zwischen Vertrauen und Optimismus und wie man sich das "erstmalige" Herausbilden von Vertrauen unter ökonomischen Akteuren vorstellen kann. Auch betrachten wir die ökonomischen Funktionen und Effekte eines Mangels oder einer Erosion von Vertrauen. Der Beitrag versucht, die wesentlichen ökonomischen Auswirkungen des Vertrauens auf das Wirtschaftswachstum, den Konjunkturzyklus, die Einkommensverteilung, etc. systematisch abzuhandeln. Schließlich widmen wir der Frage breiten Raum, welchen Beitrag das Vertrauen zum sogenannten Sozialkapital zu leisten vermag und porträtieren die Erosion von Vertrauen innerhalb, zwischen und gegenüber US-amerikanischen Firmen in Folge der weitreichenden Finanzskandale zu Beginn des neuen Millenniums.
Keywords: D23; M14; D69; 330; Unternehmenskultur; Sozialkapital; Organisationsforschung; Corporate Culture; Social Capital; Organisational Behaviour; Vertrauen; Social Capital; Wirtschaftswachstum; Betrug; Börsenkrise; Vereinigte Staaten